Silverlake fairy school / 5, bugs and butterflies - Lindsay, Elizabeth; Currey, Anna (Usborne London, 2009)
Bugs and Butterflies is every fairy's favourite magical sport, and Lila dreams of being chosen for her Clan's team at Silverlake Fairy School. Even Lila's school rival - spoilt Princess Bee Balm - is being surprisingly friendly, and appears quite sporting in her support of Lila's try-outs for the team.